التعليل الصوتي لصفات الحروف العربية - قرل, عبد المالك; بونيف, أحمد (جامعة الوادي - University of Eloued, 2021)
ملخص: إنّ الأصوات إذا تضامّت إلى بعضها شكلت مفردات، وإنّ هذا التشكيل و التأليف إنما يحصل نتيجة نسق معين، فلهذا يقال إنّ الصوت هو آلة اللفظ، و الجوهر الذي يقوم به التقطيع، و به يوجد التأليف، و لن تكون حركات اللسان لفظاً و لا كلاماً موزوناً، و لا منثوراً إلا بظهور الصوت، و لا تكون الحروف كلاماً إلا بالتقطيع و التأليف، فنؤثر السجع في المنثور أحيانا، وأحيانا أخرى نلزم أنفسنا القوافي و إقامة الوزن، ذاك أننا نبتغي من وراء كلامنا حصول الفائدة لدى الغائب و الحاضر و الراهن و الغابر، فتبدو علامات الأثر الجميل تحصل في نفس المتلقي وكل ذلك حاصل من بعد التحكم الجيد في موقعيات الحروف و الأصوات و أجراسها . من خلال هذه االبحث سنحاول الإجابة عن التساؤلات التالية :ما أهم الكيفيات العارضة للأصوات عند خروجها من موقعياتها؟،ثم ما انقساماتها وما أهميتها ؟ما دام أن حدود الحروف العربية وصفاتها باتت معروفة لدى العام و الخاص، ثم ما ملامح التعليل الصوتي لهذه العوارض و الكيفيات ؟ Abstract: Sounds, if combined with each other, form and compose vocabulary. This formation and composition take place as a result of a specific arrangement. In this sense, the sound is the instrument of articulation, the essence that the fragmentation performs, and because of it composition takes place. The movements of the tongue will not be verbal or measured speech, or prose except by the appearance of the sound. Besides, letters do not form words except by dividing and composing, so that we affect the rhyme in prose sometimes and, at other times, we commit ourselves to rhymes and establish rhythm. That is because we seek to obtain benefit at the absent, present, current and past. Therefore, the signs of the beautiful impact appear in the recipient's soul, and all of this happens due to the good command over the locations of letters , sounds and their rhyme. This article aims to answer the following questions: What are the most important types of sounds when they leave their locations? Then, what are their divisions and importance? As long as the limits of the Arabic letters and their characteristics have become known to the public and the private, then what are the features of the phonetic explanation for these supervenients and qualities?
مقال
Keywords: المخارج، الأصوات، الحروف، التأليف، الجوهر